Mercury contamination in soil, tailing and plants on agricultural fields near closed gold mine in Buru Island, Maluku - Reginawanti Hindersah; Robi Risamasu; A Marthin Kalay; Triyani Dewi; Imran Makatita (Brawijaya University, 2018)
Agricultural productivity in Buru Island, Maluku is threatened by tailings which are generated from formerly gold mine in Botak Mountain in Wamsait Village. Gold that extracted by using mercury was carried out in mining area as well agricultural field. High content of mercury in tailings and agricultural field pose a serious problem of food production and quality; and further endangers human health. The purpose of this research was to determine the contaminant level of mercury in tailing, soil and its accumulation in edible part of some food crops. Soil, tailing and plant samples for Hg testing were taken by purposive method based on mining activities in Waelata, Waeapo and Namlea sub district. Six soil samples had been analyzed for their chemical properties. Total mercury levels in tailings and plants were measured by Atomic Adsorption Spectrophotometer. This study showed that agricultural field where tailings were deposited contained Hg above the threshold but agricultural area which is far from hot spot did not. Most edible parts of food crops accumulated mercury more than Indonesian threshold for mercury content in food. This evidence explained that tailings deposited on the surface of agricultural field had an impact on soil quality and crop quality. Tailing accumulated on soil will decreased soil quality since naturally soil fertility in agricultural field in Buru is low.